1992
DOI: 10.1093/ajcn/55.1.309s
|View full text |Cite
|
Sign up to set email alerts
|

Initial studies in humans with the novel gastrointestinal lipase inhibitor Ro 18–0647 (tetrahydrolipstatin)

Abstract: Excessive intake of dietary fat contributes to the development and maintenance of both obesity and hyperlipidemia. Inhibition of gastrointestinal lipases could decrease the amount of ingested fat that is absorbed systemically by preventing the hydrolysis of triglycerides. Ro 18-0647, a chemically synthesized derivative of the natural product lipstatin, inhibits the action of gastrointestinal lipases. Initial studies in humans have shown that Ro 18-0647 can reliably increase fecal fat excretion. Ro 18-0647 has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(71 citation statements)
references
References 15 publications
0
71
0
Order By: Relevance
“…The effects of the drug on FAS are likely to have been overlooked because Orlistat is administered orally but is not significantly absorbed into the bloodstream. The drug acts in preventing absorption of dietary fat by inhibiting pancreatic lipase (another serine hy- drolase) in the digestive tract (33,34). The results of the present study indicate that Orlistat and other ␤-lactones should be considered to be a promising class of thioesterase antagonists that could be exploited for antitumor therapy.…”
Section: Discussionmentioning
confidence: 79%
“…The effects of the drug on FAS are likely to have been overlooked because Orlistat is administered orally but is not significantly absorbed into the bloodstream. The drug acts in preventing absorption of dietary fat by inhibiting pancreatic lipase (another serine hy- drolase) in the digestive tract (33,34). The results of the present study indicate that Orlistat and other ␤-lactones should be considered to be a promising class of thioesterase antagonists that could be exploited for antitumor therapy.…”
Section: Discussionmentioning
confidence: 79%
“…It inhibits the activity of pancreatic and gastric lipases, the key enzymes involved in triglyceride hydrolysis, an essential step for absorption of fat. 13 Early studies indicated that orlistat produced a dose-dependent reduction in dietary fat absorption, which is near maximal (approximately 35%) at a dose of 120 mg three times daily. 14 Its speci®c mode of action could be of particular importance since it targets one of the principal causes of weight gain, namely dietary fat.…”
Section: Introductionmentioning
confidence: 99%
“…Orlistat is a lipase inhibitor and targets fat metabolism whereas Sibutramine is a β-phenethylamine that selectively inhibits the reuptake of noradrenaline, serotonin and acts by appetite suppression mechanism. Both of these drugs have shown severe side effects like gastrointestinal disorders, cardiovascular disorders etc eliciting an immediate need to design novel strategies for combating the problem of Obesity [13][14][15]. Since obesity like hypertension is a complex diseases which arises due to multifactorial reasons, so using combination of drugs might prove effective in its treatment [16,17].…”
Section: Introductionmentioning
confidence: 99%